(untitled) (Research, Society and Development, 2022)
This review addressed the existing energy flows in the pasture ecosystem, as well as the use of organic reserves by forage grasses. The radiant energy is absorbed by the leaves and transformed into chemical energy by which the assimilated carbon is fixed. During the process of assimilation and fixation of C, photochemical, and biochemical processes are carried out, which are influenced by light. Several environmental factors can influence the ability of plants to respond to stimuli. In this sense, energy flows within the pasture system are in constant movement to maintain the forage plant. The direction of energy flow varies with the growth environment of the forage plant, since in addition to affecting the structural characteristics, the environmental factors exert control over the root system. In theory, organic reserves located in roots and stems play a crucial role in the growth of grazed plants, especially in the first days after defoliation. Therefore, it is important to encourage research involving the reserve organs and their accumulation patterns so that the results can assist in the development of sustainable grazing systems.